Peran Pesantren Dalam Kaderisasi Dakwah - Feri Sarnandes; Syahbuddin zakaria (AL-QOLAM : Jurnal Dakwah dan Pemberdayaan Masyarakat, 2021)
Islamic boarding schools in essence not only prepare their students to become human beings who have religious character and are knowledgeable, but also develop the psychology of their students to become individuals who are sensitive and care about their environment. Awareness of the surrounding environment is the main provision of a preacher's passion, because without awareness and concern, the slogan of the preaching of wahamar ma'ruf nahimunkar will not be realized. The concept of Islamic boarding school education is deliberately designed in such a way that the students who later graduate become human resources who are ready to preach Islamic values wherever they are.